2004
DOI: 10.1152/japplphysiol.00262.2004
|View full text |Cite
|
Sign up to set email alerts
|

Cyclical elongation regulates contractile responses of isolated airways

Abstract: .-Bronchoconstrictor responses are quantitatively different when they are evoked under static conditions and during or after periods of deep inspiration. In vivo, deep inspirations produce bronchodilation and protect the lung from subsequent bronchoconstriction (termed bronchoprotection). These effects may be due in part to dynamic stretch on airways produced by cyclical expansion of airway diameter. However, airways also lengthen cyclically during breathing. The effects of cyclical airway elongation on evoked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 35 publications
(55 reference statements)
0
25
1
Order By: Relevance
“…WANG et al [69] found that periodic stretching of isolated porcine ASM in the relaxed state resulted in a decrease of force production with subsequent contractions. However, pressure oscillation in isolated airway segments that periodically strained the ASM embedded within the segment led to a slight increase of the pressure generated in the subsequent isovolumic ''constriction'' [295,296]. Airways were subjected to either radial [295] or axial [296] distension, with similar findings.…”
Section: Other Modulators Of Asmmentioning
confidence: 70%
See 3 more Smart Citations
“…WANG et al [69] found that periodic stretching of isolated porcine ASM in the relaxed state resulted in a decrease of force production with subsequent contractions. However, pressure oscillation in isolated airway segments that periodically strained the ASM embedded within the segment led to a slight increase of the pressure generated in the subsequent isovolumic ''constriction'' [295,296]. Airways were subjected to either radial [295] or axial [296] distension, with similar findings.…”
Section: Other Modulators Of Asmmentioning
confidence: 70%
“…However, pressure oscillation in isolated airway segments that periodically strained the ASM embedded within the segment led to a slight increase of the pressure generated in the subsequent isovolumic ''constriction'' [295,296]. Airways were subjected to either radial [295] or axial [296] distension, with similar findings. Radial strain increased ASM length, whereas under the experimental conditions applied, axial distension reduced ASM length.…”
Section: Other Modulators Of Asmmentioning
confidence: 70%
See 2 more Smart Citations
“…After the dissection and excision of the bronchial segment, side branches were tightly ligated with surgical silk (4-0) as previously mentioned (Mitchell et al, 1998;Khangure et al, 2004). The ligated bronchial segment was then mounted horizontally in a 30-ml Mayflower organ bath (Hugo Sachs Elektronik-Harvard Apparatus GmbH, March-Hugstetten, Germany) containing warmed modified Krebs buffer solution (37°C) gassed with carbogen (95% O 2 -5% CO 2 ) as previously mentioned by Mitchell and Sparrow (1994) with modifications.…”
Section: Methodsmentioning
confidence: 99%